2022
DOI: 10.1109/tbme.2022.3177006
|View full text |Cite
|
Sign up to set email alerts
|

From Skin Mechanics to Tactile Neural Coding: Predicting Afferent Neural Dynamics During Active Touch and Perception

Abstract: First order cutaneous neurons allow object 2 recognition, texture discrimination, and sensorimotor 3 feedback. Their function is well-investigated under passive 4 stimulation while their role during active touch or 5 sensorimotor control is understudied. To understand how 6 human perception and sensorimotor controlling strategy 7 depend on cutaneous neural signals under active tactile 8 exploration, the finite element (FE) hand and Izhikevich 9 neural dynamic model were combined to predict the 10 cutaneous neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The bone is a stiff connective tissue that supports body parts and is the mechanical basis for movement. 37 38 Bone is often simplified into a macroscopic solid and modeled using elastic isotropic constitutive laws. In most simulations, bone is divided into two different types: cortical/compact bone and cancellous/trabecular bone.…”
Section: Resultsmentioning
confidence: 99%
“…The bone is a stiff connective tissue that supports body parts and is the mechanical basis for movement. 37 38 Bone is often simplified into a macroscopic solid and modeled using elastic isotropic constitutive laws. In most simulations, bone is divided into two different types: cortical/compact bone and cancellous/trabecular bone.…”
Section: Resultsmentioning
confidence: 99%
“…The hit rate of the ATSS increased with the curvature of the object because the firing rate and Victor-Purpura distance are larger than those initiated by being in contact with the baseline object. Our previous research demonstrated that a more intense variation of hand contact strain/stress could be imitated when touching the object with a larger surface curvature 40 . This leads to a larger membrane current through cutaneous receptors and more intense neural spiking.…”
Section: Discussionmentioning
confidence: 99%
“…The tactile signals elicited from the first-order neurons were then computed through the Izhikevich neural dynamic model based on the membrane current flow over the cutaneous receptor. The detailed process of predicting the human afferent tactile signals was illustrated in our previous research 40 .…”
Section: Saimentioning
confidence: 99%
“…However, the FE models alone cannot prescribe whether the tactile receptors are activated due to the stimulus. Therefore, certain studies employed a FE mechanical model combined with a neurophysiological model, i.e., mechano-neurophysiological model (Gerling et al, 2014;Hamasaki and Yamada, 2021;Wei et al, 2022). Gerling et al (2014) evaluated the neural responses of slowly adapting type-1 (SA1) afferents against the contact of an indentor with a finger pad.…”
Section: Introductionmentioning
confidence: 99%